A senataxin-associated exonuclease SAN1 is required for resistance to DNA interstrand cross-links - Alex M. Andrews (Nature Portfolio, 2018)
When DNA interstrand cross-links damage occurs, it causes disruption of replication and transcription. Here the authors identify FAM120B/SAN1, a 5′ exonuclease involved in the repair process of Interstrand Crosslinks independently of the Fanconi Anemia pathway.